PENGARUH KONSERVATISME AKUNTANSI DAN FAKTOR LAINNYA TERHADAP PENGHINDARAN PAJAK - Kevin Hartanto; Fanny Anggraeni (E-Jurnal Akuntansi TSM, 2023)
This research was conducted to examine the factors that influence tax avoidance. Some of these factors are sales growth, profitability, leverage, company size, proportion of independent commissioners, accounting conservatism, capital intensity ratio, and inventory intensity ratio. The purpose of this research is to obtain empirical evidence regarding the effect of sales growth, profitability, leverage, firm size, proportion of independent commissioners, accounting conservatism, capital intensity ratio, and inventory intensity ratio on tax avoidance in non-financial companies. The population of this study are non-financial companies listed on the Indonesia Stock Exchange (IDX) during 2019-2021. Sampling in this study used a purposive sampling method and obtained 155 non-financial companies so that the total data in this study were 465 data. The data were analyzed by multiple regression analysis. The results of this study indicate that profitability and firm size have a positive effect on tax avoidance. Leverage has a negative effect on tax avoidance, while sales growth, proportion of independent commissioners, accounting conservatism, capital intensity ratio, and inventory intensity ratio have no effect on tax avoidance.